2023
DOI: 10.3390/educsci13040418
|View full text |Cite
|
Sign up to set email alerts
|

Arab Teachers’ Well-Being upon School Reopening during COVID-19: Applying the Job Demands–Resources Model

Abstract: Once the major threat of the COVID-19 pandemic diminished, schools reopened, and teachers once again had to cope with unprecedented challenges. The impact of these challenges on the emotional well-being of Arab teachers, who have a unique set of challenges within the Israeli school educational system, has received little attention in the recent literature. In this cross-sectional study, we examined 300 Arab teachers’ well-being in Israel in May 2021, three months after schools were reopened. All study hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 70 publications
1
4
0
Order By: Relevance
“…It (i.e., the ability to bounce back from negative emotional experiences) appeared to enable teachers to overcome the challenges caused by the pandemic and protect themselves from overwhelmingly excessive feelings of stress. This confirms studies conducted during the COVID-19 pandemic, which found that teachers' resilience was positively related to their emotional state and resilience [11,17]. A recent review of scientific evidence on the positive aspects of the trauma of the COVID-19 pandemic found that resilience was associated with lower levels of depression, anxiety, and burnout among health professionals.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…It (i.e., the ability to bounce back from negative emotional experiences) appeared to enable teachers to overcome the challenges caused by the pandemic and protect themselves from overwhelmingly excessive feelings of stress. This confirms studies conducted during the COVID-19 pandemic, which found that teachers' resilience was positively related to their emotional state and resilience [11,17]. A recent review of scientific evidence on the positive aspects of the trauma of the COVID-19 pandemic found that resilience was associated with lower levels of depression, anxiety, and burnout among health professionals.…”
Section: Discussionsupporting
confidence: 82%
“…Alongside teachers' feelings of emotional distress, a few studies observed positive changes among teachers as a result of dealing with the COVID-19 crisis [11][12][13]. Some of these changes include increased care, security, self-direction, short-time work, and increases in leisure time.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research in this field recognizes the complexity of emotions, especially when trying to define or delimit them, as well as the short-and long-term effects of home confinement on both teachers and students. In fact, these investigations show a negative impact at the psychological, emotional, and behavioral levels that involves changes in routines, changes at the physical level, and even the use of screens [5,6]. This scenario can be influenced by the functioning of other interconnected domains, among which family, school, and society may be involved.…”
Section: The Relevance Of Emotions In the Field Of Educationmentioning
confidence: 99%